Low-Cost Robot Focused on Teaching Advanced of Mobile Robotics Techniques - Martinelli, Dieisson; Sousa, Alex; Augusto, Mario; Kalempa, Vivian; Oliveira, Andre; Teixeira, Marco (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This work proposes the development of a low-cost autonomous robot for academic purposes. The robot is developed from parts not initially developed for robotics, such as a vacuum cleaner. As a processor, the robot uses a Raspberry Pi associated with the ROS framework. The developed robot is capable of performing Simultaneous Localization and Mapping (SLAM) actions. The goal is to use the proposed robot in the classroom to teach mobile robotics to students and researchers. To validate the use of the robot in the classroom, a SLAM class was held where one class had contact with the robot and another did not. The class that had contact with the robot presented better results in the questionnaire about the subject.